Hubungan Berat Badan Bayi Lahir Dengan Ruptur Perineum Pada Persalinan Normal Di Kamar Bersalin Rumah Sakit Umum Anutapura Palu - Enggar, Enggar; Anna V. Pont (Akademi Kebidanan Palu Sulawesi Tengah, 2019)
Perineal rupture occur due to the spontaneous rupture or episiotomy. Episiotomy is performed on large infants, perineal stiffness, delivery with fetal abnormal position, and forceps and vacuum delivery.Perineal tearcan cause woman’s discomfort. Birth weight is the baby's weight weighed in the first 24 hoursafterbirth. The more weight the baby has will increase the risk of perineal rupture. This study aimed to determine the corelation between Body Weight and Perineal Rupture in Normal Delivery in the Maternity Room of Anutapura Hospital Palu. This study was analytic descriptive study with 252 samples taking by simple random sampling, which was by drawing the member of the population (lottery technique). The results showed that the normal birth weight had the highest number of 203 infants (80.6%). Meanwhile abnormal birth weight had 49 infants (19.4%) and normal birth weight showed the highest number of perineal ruptures that were 138 infants (54.8%), whereasabnormal birth weight was the lowest number of perineal ruptures with 114 infants (45.2%). Based on the data, the results obtained 26.95> Chi square table 0.05 of 3.841. It means that there is a statistically corelation between infant birth weight and perineal rupture on normal delivery. Thus, it is expected for health workers to be able to control the speed and regulation of the birth of the head, and lead the mother to carry it correctly to prevent the occurrence of perineal rupture.